2009
DOI: 10.3354/meps08189
|View full text |Cite
|
Sign up to set email alerts
|

Topical and trophic relationships in a boring polychaete–scallop association: fatty acid biomarker approach

Abstract: The association between the Japanese scallop Patinopecten yessoensis and the scallopshell-boring polychaete worm Polydora brevipalpa was investigated in the natural environment. Fatty acid analyses were performed on the scallop, polychaete, and potential food materials available in the environment, with the aim of determining the main food sources of these animals and the trophic relationships between species. The scallop and the polychaete showed a similarity in their fatty acid compositions. High concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
3

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
3
12
0
3
Order By: Relevance
“…FA trophic markers have long been recognized as efficient tools in studies of marine food webs (Sargent et al 1989, Budge et al 2002, 2006, Dalsgaard et al 2003. Recent studies have demonstrated that FAs can be successfully used to elucidate feeding ecology and trophic relationships of marine fish (Drazen et al 2009, Stowasser et al 2009) and invertebrates (Silina & Zhukova 2009, Spilmont et al 2009). However, northern/temperate and abyssal marine ecosystems have been the focus of most research efforts, and FA data regarding trophic interactions in tropical marine ecosystems are scarce (reviewed by Dalsgaard et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…FA trophic markers have long been recognized as efficient tools in studies of marine food webs (Sargent et al 1989, Budge et al 2002, 2006, Dalsgaard et al 2003. Recent studies have demonstrated that FAs can be successfully used to elucidate feeding ecology and trophic relationships of marine fish (Drazen et al 2009, Stowasser et al 2009) and invertebrates (Silina & Zhukova 2009, Spilmont et al 2009). However, northern/temperate and abyssal marine ecosystems have been the focus of most research efforts, and FA data regarding trophic interactions in tropical marine ecosystems are scarce (reviewed by Dalsgaard et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Starvation of Yeso scallop in wild populations from the study area has never been mentioned in a literature. This scallop feeds on a mixed, but diatom-dominated phytoplankton diet (Silina & Zhukova, 2009). According to some estimates, the diatom genera Thalassiosira, Coscinodiscus, Pseudo-nitzschia, Chaetoceros, Thalassionema, Rhizosolenia, and Skeletonema account for about 60–90% of the total phytoplankton biomass in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Спектр питания камчатского краба в губе Дальнезеленецкая довольно широк (Павлова, 2008; Дворецкий, 2012а): он включает более 40 видов донных беспозвоночных, среди которых наиболее часто встречаются двустворчатые и брюхоногие моллюски, морские ежи, морские звезды, офиуры, ракообразные и полихеты. Исследования биохимического состава донных животных показали, что содержание жирных кислот сильно варьирует в зависимости от таксономического статуса объекта (Howell et al, 2003;Drazen et al, 2008;Silina, Zhukova, 2009). Например, концентрация ДГК в тканях ракообразных и иглокожих обычно выше, чем в тканях полихет (Howell et al, 2003;Drazen et al, 2008), а концентрация арахидоновой кислоты у моллюсков почти в три раза выше, чем у полихет (Silina, Zhukova, 2009).…”
Section: результаты и обсуждениеunclassified
“…Исследования биохимического состава донных животных показали, что содержание жирных кислот сильно варьирует в зависимости от таксономического статуса объекта (Howell et al, 2003;Drazen et al, 2008;Silina, Zhukova, 2009). Например, концентрация ДГК в тканях ракообразных и иглокожих обычно выше, чем в тканях полихет (Howell et al, 2003;Drazen et al, 2008), а концентрация арахидоновой кислоты у моллюсков почти в три раза выше, чем у полихет (Silina, Zhukova, 2009). Таким образом, можно с высокой долей вероятности утверждать, что основную роль в изменчивости жирнокислотного состава гемолимфы отдельных особей краба имеют не физиологические параметры животных, а то, какие объекты были употреблены ими в пищу.…”
Section: результаты и обсуждениеunclassified